Associations between volume changes and spatial dose metrics for the urinary bladder during local versus pelvic irradiation for prostate cancer. (4th May 2017) - Casares-Magaz, Oscar; Moiseenko, Vitali; Hopper, Austin; Pettersson, Niclas Johan; Thor, Maria; Knopp, Rick; Deasy, Joseph O.; Muren, Ludvig Paul; Einck, John
Abstract: Background: Inter-fractional variation in urinary bladder volumes during the course of radiotherapy (RT) for prostate cancer causes deviations between planned and delivered doses. This study compared planned versus daily cone-beam CT (CBCT)-based spatial bladder dose distributions, for prostate cancer patients receiving local prostate treatment (local treatment) versus prostate including pelvic lymph node irradiation (pelvic treatment). Material and Methods: Twenty-seven patients (N = 15 local treatment; N = 12 pelvic treatment) were treated using daily image-guided RT (1.8 Gy@43-45 fx), adhering to a full bladder/empty rectum protocol. For each patient, 9-10 CBCTs were registered to the planning CT, using the clinically applied translations. The urinary bladder was manually segmented on each CBCT, 3 mm inner shells were generated, and semi and quadrant sectors were created using axial/coronal cuts. Planned and delivered DVH metrics were compared across patients and between the two groups of treatment ( t -test, p < .05; Holm–Bonferroni correction). Associations between bladder volume variations and the dose-volume histograms (DVH) of the bladder and its sectors were evaluated (Spearman's rank correlation coefficient, r s ). Results: Bladder volumes varied considerably during RT (coefficient of variation: 16–58%). The population-averaged planned and delivered DVH metrics were not significantly different at any dose level. Larger treatment bladder volumes resulted in increased absolute volume of the posterior/inferior bladder sector receiving intermediate-high doses, in both groups. The superior bladder sector received less dose with larger bladder volumes for local treatments ( r s ± SD: −0.47 ± 0.32), but larger doses for pelvic treatments ( r s ± SD: 0.74 ± 0.24). Conclusions: Substantial bladder volume changes during the treatment course occurred even though patients were treated under a full bladder/daily image-guided protocol. Larger bladder volumes resulted in less bladder wall spared at the posterior-inferior sector, regardless the treatment received. Contrary, larger bladder volumes meant larger delivered doses to the superior bladder sector for pelvic RT but smaller doses for local treatments. Graphical Abstract: